Algorithm to read various sensors to detect the hazardous parameters in industry - Singh, Rajesh; Samkaria, Rohit; Gehlot, Anita; kumar Singh, Neeraj; Rawat, Kaushal; De, Aisik; Rahiman, Adil (International Journal of Engineering and Technology, 2018)
In the construction and coal mine industry various accident statistics indicates the fatalitiesand serious injuries due to the hazardous con-fined areas. The most cases occurs due to the lack of the oxygen, poisonous gasesand temperature extremes shown in the review of inter-national safety regulation review which has the major contribution to make these area hazardous. In order to reduce these health and safety hazards the works proposed is based on the wireless sensor area network technology to monitor various parameters which may lead to haz-ardous condition so that the early warning of hazards can give and casualties which occurs unknown parameters may reduce. The developed model having the database design with management to monitoring system with the help of desktop application. The hazardous indication warning is transmitted to base station by different wireless node and received at base station.